2018
DOI: 10.1111/sms.13084
|View full text |Cite
|
Sign up to set email alerts
|

Knee‐high compression socks minimize head‐up tilt‐induced cerebral and cardiovascular responses following dynamic exercise

Abstract: In healthy individuals during a non-exercised state, knee-high compression socks (CS) may reduce the magnitude of lower limb venous pooling during orthostasis but are not effective at minimizing the incidence of pre-syncopal symptoms. However, exaggerated reductions in cerebral blood flow velocity (CBV) and cardiac stroke volume (SV) occur during passive head-up tilt (HUT) testing following dynamic exercise. It is unknown if CS can minimize post-exercise HUT-induced decrements in CBV and SV in this population.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 30 publications
4
26
0
Order By: Relevance
“…This change in heart rate and lack of change in mean arterial blood pressure has been previously reported by standard non‐active compression garments (Dorey et al. ). This suggests that these active garments act similarly as normal compression garments.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…This change in heart rate and lack of change in mean arterial blood pressure has been previously reported by standard non‐active compression garments (Dorey et al. ). This suggests that these active garments act similarly as normal compression garments.…”
Section: Discussionsupporting
confidence: 83%
“…; Dorey et al. ). The body will attempt to compensate by increasing heart rate and blood pressure through the baroreceptor reflex.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, they showed that pre-syncope was correlated with muscle oxygenation elevation, decreased skin blood flow and oxygenation (Lund et al, 2017). Considering practical implications Dorey et al (2018) proposed using of knee-high compression socks in order to reduce the prevalence of syncope after physical exercise due to diminishing reduction in SV and thus cerebral blood flow velocity after moderate intensity. Ruzieh et al (2018) showed that Closed Loop Stimulation pacing was effective in HUTT(+) patients being in the age of 40 years or older with cardio-inhibitory response.…”
Section: Discussionmentioning
confidence: 99%